CSR dan Nilai Perusahaan: Peran Odd-Even Effect Dewan Direksi, Umur dan Ukuran Perusahaan - Dewi, Ayu Aryista; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
Firm value is one indicator in investing. The study aims to examine the effect of Corporate Social Responsibility (CSR) on firm value by using firm age, board of directors odd-even effect and company size as moderating variables for companies listed on the Sri Kehati Index from 2013-2019. The research sample consisted of 84 observations and data were analyzed using multiple linear regression models and Moderated Regression Analysis (MRA). The results of the study show that CSR has a positive and significant effect on firm value. The results also show that firm age, board of directors odd-even effect and firm size moderate the relationship between CSR and firm value. Keywords: Board Meeting Efficiency; Company Value; Corporate Social Responsibility; Company Size; Company Age